PEMBELAJARAN REMEDIAL SEBAGAI CARA MENGATASI KESULITAN BELAJAR SISWA: STUDI KEPUSTAKAAN - Nur Aisyah Agustin Bakhri; Deliani, Nurfarida; Batubara, Juliana (Tarbiya Islamica, 2025)
Education is something that strives to create an active learning environment and process for students, as well as a platform for developing their potential. However, every child has a different learning process and outcome, which is why teachers are required to be able to make the learning process active and conducive. There are many things that interfere with the learning process, also known as learning difficulties. Learning difficulties vary from student to student, some caused by physical, psychological, or social factors. Learning difficulties in students can interfere with their learning outcomes. Therefore, to overcome this, teachers need to diagnose learning difficulties in students and improve unsatisfactory learning outcomes by providing remedial learning. The method used was qualitative library research. The results of this study indicate that remedial learning greatly improves the learning outcomes of students who experience learning difficulties. Because remedial learning is not just about repeating lessons, but also helping students learn according to their needs and in a very focused manner. Remedial learning is provided to students whose learning outcomes are unsatisfactory. Remedial learning is conducted individually so that students can focus better, and the learning methods are tailored to the types of learning difficulties experienced by students.